2021
DOI: 10.3389/fcimb.2021.698909
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Novel Polyvalent Bacteriophages With Potent In Vitro Activity Against an International Collection of Genetically Diverse Staphylococcus aureus

Abstract: Phage therapy recently passed a key milestone with success of the first regulated clinical trial using systemic administration. In this single-arm non-comparative safety study, phages were administered intravenously to patients with invasive Staphylococcus aureus infections with no adverse reactions reported. Here, we examined features of 78 lytic S. aureus phages, most of which were propagated using a S. carnosus host modified to be broadly susceptible to staphylococcal phage infection. Use of this host elimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 65 publications
3
7
0
Order By: Relevance
“…To demonstrate the differences in efficacy depending on the characteristics of the strain, the phages COP-80A, COP-80B, and COP-110 were tested on the production host COB-Sec1 and biofilm proficient clinical isolate COB-SE3. They were significantly more effective against the production organism for all MOIs tested, but the time they inhibited the growth of COB-SE3 was still longer than 15 h, which is similar to previous observations ( Alves et al., 2014 ; Whittard et al., 2021 ). Since biofilm is critical for virulence of S. epidermidis , the effect on mature 24 h-old biofilm was examined using bright field microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…To demonstrate the differences in efficacy depending on the characteristics of the strain, the phages COP-80A, COP-80B, and COP-110 were tested on the production host COB-Sec1 and biofilm proficient clinical isolate COB-SE3. They were significantly more effective against the production organism for all MOIs tested, but the time they inhibited the growth of COB-SE3 was still longer than 15 h, which is similar to previous observations ( Alves et al., 2014 ; Whittard et al., 2021 ). Since biofilm is critical for virulence of S. epidermidis , the effect on mature 24 h-old biofilm was examined using bright field microscopy.…”
Section: Discussionsupporting
confidence: 90%
“…The experimental ndings by Whittard et al observed the appearance of Pacman-like colonies (described as half-lysis colony type in this study) during phage-bacterial interaction, and they also found that most of them were susceptible to phage although they remained resistant to phage in the liquid medium (Whittard et al 2021). A study by Głowacka-Rutkowska et al demonstrated the equilibration of phage bacteria in a mixture in which the authors outlined that phage carrier state cells and phage resistant coexist in a mixture, and the resistant phenotype can be reverted upon removing the phage by subculturing (Glowacka-Rutkowska et al 2018).…”
Section: Discussionsupporting
confidence: 69%
“…They also participate in the transmission of pathogenicity islands and are the primary carrier of chromosomal and extrachromosomal genes during horizontal gene transfer (HGT) [ 31 ]. Phages can transfer genes of various staphylococcal virulence factors, including Panton–Valentine leucocidin, staphylokinase, enterotoxins, chemotaxis inhibitory proteins, and exfoliative toxins [ 32 , 33 ]. This may explain the association between the sensitivity of S. aureus to some phages and their pathogenicity.…”
Section: Discussionmentioning
confidence: 99%